EFEK WAKTU PEMBERIAN PUPUK KOMPOS TERHADAP HASIL DAN KADAR KLOROFIL DAUN TANAMAN TOMAT (Solanum lycopersicum L.) - , YENI NUR MALASARI; , Drs. Sudjino, M.S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tomato is horticultular plant that has many advantages. Its fruit can be used as raw material for some processes product, so it has high economic value. Not all tomato that is used for raw materials has good quality. Low quality tomatoes can be caused by a not right timing in giving nutrients during the growth and development of the plant. Therefore it is necessary examine the effect of time variation of giving compost fertilizer from 0 weeks to VI weeks after planting towards the productivity and leaves chlorophyll level in tomato plants. In this research, weused 2 weeks tomatoâs seedlings. At the harvest time, tomatoes were taken to determine the average weight of fruits, average volume of fruits, the amount of fruits that produced, and all parts of the roots, stems, leaves to determine the wet weight, dry weight, and water content of the plants. Tomato leaves were taken during flowering time and green fruiting to determine chlorophyll levels. The results showed that the best dry weight of plants , the wet weight of plants, the water content , average fruit weight , average fruit volume , number of fruits per plant, levels of total a and b chlorophyll tomato leaves during flowering and green fruiting by giving compost fertilizer at time intervals from III weeks until V weeks after planting.